2016
DOI: 10.1155/2016/4091461
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxidative Stress on Stored Platelets

Abstract: Platelet storage and its availability for transfusion are limited to 5-6 days. Oxidative stress (OS) is one of the causes for reduced efficacy and shelf-life of platelets. The studies on platelet storage have focused on improving the storage conditions by altering platelet storage solutions, temperature, and materials. Nevertheless, the role of OS on platelet survival during storage is still unclear. Hence, this study was conducted to investigate the influence of storage on platelets. Platelets were stored for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
1
17
1
1
Order By: Relevance
“…As already shown by Skripchenko et al [39], we demonstrated a significant increase in ROS production from day 3 after storage. This suggests that, contrary to the study by Manasa and Vani [37], the platelet antioxidant system prevent oxidative stress progression endures for 3 days in banked PCs under conditions of continuous agitation. It is important to know that without pre-storage leukoreduction PCs inevitably include a residual amount of leukocytes which, although their concentration is very low, may contain much higher levels of ROS than platelets, especially when they form aggregate with platelets [40].…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…As already shown by Skripchenko et al [39], we demonstrated a significant increase in ROS production from day 3 after storage. This suggests that, contrary to the study by Manasa and Vani [37], the platelet antioxidant system prevent oxidative stress progression endures for 3 days in banked PCs under conditions of continuous agitation. It is important to know that without pre-storage leukoreduction PCs inevitably include a residual amount of leukocytes which, although their concentration is very low, may contain much higher levels of ROS than platelets, especially when they form aggregate with platelets [40].…”
Section: Discussioncontrasting
confidence: 92%
“…In addition, platelet dysfunction reported in patients with genetically determined impaired O 2 -formation can provide further supporting evidence for the importance of ROS generation in eliciting platelet activation [18,36]. However, whether platelet oxidative changes first induce platelet activation or whether platelet stimulation with activating agonists triggers ROS generation is still not defined unambiguously [37]. Platelet storage is also associated with ROS generation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…During storage, platelet lactate levels rise, platelet additive solution becomes progressively acidotic, and in vitro platelet responses to agonists such as thrombin and collagen decrease substantially . Oxidative stress also increases in stored platelets, depleting their antioxidant defense mechanisms . Together, these changes may lead to altered platelet function and in vivo aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because the mature platelet does not contain a nucleus, it lacks the machinery to repair oxidative mtDNA damage, thereby creating a condition wherein platelet mtDNA may undergo cycles of replication and degradation (24). In light of these considerations, it is tempting to speculate that an oxidant-enriched environment in stored platelets (25, 26) leads to oxidative mtDNA damage and attendant elaboration of mtDNA DAMPs (8, 17), which may, in turn, contribute to the limited shelf-life of platelets (27). …”
Section: Discussionmentioning
confidence: 99%